Clinical impact of soluble Neuropilin-1 in ovarian cancer patients and its association with its circulating ligands of the HGF/c-MET axis - Klotz, Daniel Martin; Kuhlmann, Jan Dominik; Link, Theresa; Goeckenjan, Maren; Hofbauer, Lorenz C.; Göbel, Andy; Rachner, Tilman D.; Wimberger, Pauline (Frontiers in Oncology, 2022)
Background: Neuropilin (NRP) is a transmembrane protein, which has been proposed as pro-angiogenic mediator and potential driver of cancer progression. NRP-1 up-regulation in ovarian cancer tissue predicts poor prognosis, however, the clinical relevance of the soluble form of NRP-1 (sNRP-1) as a circulating biomarker in ovarian cancer patients is unknown. Methods/patients cohort: sNRP-1 levels were quantified in a cohort of 88 clinically documented ovarian cancer patients by a commercially available sNRP-1 enzyme-linked immunosorbent assay (ELISA) kit (Biomedica, Vienna, Austria). Patients (81.8% with FIGOIII/IV) received primary cytoreductive surgery with the aim of macroscopic complete resection (achieved in 55.7% of patients) and the recommendation of adjuvant chemotherapy in line with national guidelines. Results: Higher levels of sNRP-1 reflected more advanced disease (FIGO III/IV) and indicated a trend towards suboptimal surgical outcome, i.e. any residual tumor. sNRP-1 was neither related to the patients’ age nor the BRCA1/2 mutational status. Patients with higher sNRP-1 levels at primary diagnosis had a significantly reduced progression-free survival (PFS) (HR = 0.541, 95%CI: 0.304 - 0.963; p = 0.037) and overall survival (OS) (HR = 0.459, 95%CI: 0.225 - 0.936; p = 0.032). Principal component analysis showed that sNRP-1 levels were unrelated to the circulating biomarkers Hepatocyte growth factor (HGF) and the soluble ectodomain of its receptor the tyrosine kinase mesenchymal–epithelial transition (cMET), suggesting that there is no proportional serological concentration gradient of soluble components of the NRP-1/HGF/cMET signaling axis. Conclusions: In line with the previously shown tissue-based prognostic role, we demonstrated for the first time that sNRP-1 can also act as a readily accessible, prognostic biomarker in the circulation of patients with ovarian cancer at primary diagnosis. Given its known role in angiogenesis and conferring resistance to the Poly ADP-ribose polymerase (PARP) inhibitor olaparib in vitro, our exploratory results encourage more detailed investigations of sNRP-1 as a potential predictive biomarker for bevacizumab and/or PARP-inhibitor treatment.